PEMANFAATAN ALAT PERAGA BATANG NAPIER DALAM PEMBELAJARAN OPERASI PERKALIAN SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA - Prihastini Oktasari Putri (Academy of Education Journal, 2019)
This study aims to determine whether using napier rods can improve student mathematics learning outcomes. The method used in this study is quasi-experimental. The type of research isor Classroom Action ResearchClassroom Action Research (CAR)(CAR). The sample in this study were all students of class IV SD 2 Wadasmalang in the 2018 academic year 2018 as many as 24 students. The instrument used in this study was a student achievement test. Based on the results of the study, it was concluded that the use of napier rod props can improve student learning outcomes in mathematics class IV at SD Negeri 2 Wadasmalang. This can be shown at the end of the cycle test results turned out to be obtained a significant increase in value, meaning that the process of learning mathematics by using the napier rod props the average value of the class has increased with the results on pre-cycle of 51.67; the first cycle was 66.67 and the second cycle was 78.89. With the percentage of completeness in pre-cycle of 25%, the first cycle of 66.67% and the second cycle of 83.34%.